FRI0373 Long-term follow-up of 320 children born to mothers with systemic autoimmune diseases: a multicentre italian survey from 24 rheumatology centres. (12th June 2018) - Lazzaroni, M.G.; Nalli, C.; Andreoli, L.; Carini, C.; Bartoloni-Bocci, E.; Gerli, R.; Chighizola, C.B.; Gerosa, M.; Meroni, P.L.; Sinigaglia, L.; Conigliaro, P.; Perricone, R.; et al.
Abstract : Background: Rheumatic Diseases (RD) frequently affect women during reproductive age, therefore counselling on family planning is crucial for their quality of life. Children's outcome is a major topic, but no large studies are available. Objectives: To assess the long-term health conditions of children born to women with RD in a large multicentre cohort. Methods: 24 Rheumatology Centres distributed the questionnaire (65 multiple-choice and 12 open-answer questions) to consecutive patients (18–55 years) in September 2015. Data were analysed dividing children upon maternal diagnosis: Chronic Arthritides (CA) and Connective Tissue Diseases (CTD). Results: Data were collected for 320 children (166 males, 52%) born to 184 mothers (63 CA and 121 CTD). At the time of interview, children had a mean age of 17.1±9.6 years. Preterm delivery (<37 w) was observed in 72 cases (22.5%), including 13 (4%)<34 w. Data on autoimmune/inflammatory disease (AIID) and/or neurodevelopmental disorders (ND)/learning disabilities (LD) is reported in table 1. 12 children (3.7%) had a diagnosis of AIID, mostly coeliac disease (8/12, 67%)and 11 children (3.4%) of a ND and/or LD by a Paediatric Neuropsychiatrist. To rule out the possible effects of in utero exposure to maternal autoantibodies and/or anti-rheumatic drugs in the pathogenesis of ND, these data were retrieved for 280 children (88%) and a comparison was performed between 11 affected and 269 not-affected children (table 2). Conclusions: In this long-term follow-up of children born to mothers with RD in this large, multicenter study of randomly interviewed women each AIID did not display a significantly increased frequency as compared to the literature; only coeliac showed a mild increased frequency. Children with LD had a tendency to cluster in the group of mothers with CTD, especially after maternal diagnosis (4/63, 6.3%), with a higher frequency as compared to general paediatric population. No significant relationships between ND/LD and prematurity, intrauterine drug exposure or maternal autoantibodies were identified. Acknowledgements: Statistical analysis supported by an unrestricted grant by UCB Pharma. The authors wish to thank Patients Associations and Participants to the survey. Disclosure of Interest: None declared